Beyond basic statistics : tips, tricks, and techniques every data analyst should know - Jarman, Kristin H. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
This book presents the more subjective side of statistics-the art of data analytics. Each chapter explores a different question using fun, common sense examples that illustrate the concepts, methods, and applications of statistical techniques. Without going into the specifics of theorems, propositions, or formulas, it demonstrates statistics as a useful problem-solving tool. It features: examples throughout aimed to strengthen readers' understanding of statistical concepts and methods; a step-by-step approach to elementary statistical topics such as sampling, hypothesis tests, outlier detection, normality tests, robust statistics, and multiple regression; case studies that illustrate the use of the presented techniques; highlights of well-known shortcomings that can lead to false conclusions; and an introduction to advanced techniques such as validation and bootstrapping. --
Machine generated contents note: 1.Introduction: It Seemed like the Right Thing to Do at the Time -- 2.The Type A Diet: Sampling Strategies to Eliminate Confounding and Reduce Your Waistline -- 3.Conservatives, Liberals, and Other Political Pawns: How to Gain Power and Influence with Sample Size Calculations -- 4.Bunco, Bricks, and Marked Cards: Chi-Squared Tests and How to Beat a Cheater -- 5.Why it Pays to be a Stable Master: Sumo Wrestlers and Other Robust Statistics -- 6.Five-Hour Marriages: Continuous Distributions, Tests for Normality, and Juicy Hollywood Scandals -- 7.Believe It or Don't: Using Outlier Detection to Find the Weirdest of the Weird -- 8.The Battle of the Movie Monsters, Round Two: Ramping up Hypothesis Tests with Nonparametric Statistics -- 9.Models, Murphy's Law, and Public Humiliation: Regression Rules to Live By.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mathematical statistics -- Popular works; Mathematical statistics; Popular works; Electronic books; Electronic books